Design of Submicroscopic Book and Improving of Students Learning Outcomes for Remedial Program in Class XI for Buffer Solution - Sabatinie, Indrie; Susilaningsih, Endang; Kurniawan, Cepi (Journal of Innovative Science Education, 2019)
This study aims to develop the submicroscopic book and improving of students learning outcomes for remedial programs. A remedial program is one of the lessons used to improve student understanding and learning outcomes. The results of a survey conducted by researchers at 10 SMA/ MA in Cirebon that the implementation of remedial program rarely carried out remedial teaching activities due to time constraints. This research used R & D method with 4-D model which consists of 4 stages, that were define, design, develop, and dessimination. The results of a small scale test that there was an inproving in students learning outcomes after participating in the remedial program, from 17.14% to 58.62%. The results of a large scale test were carried out in two classes with an increase in student learning outcomes from 12.50% to 71.43% and 17.50% to 78.79%. Students gave the positive responses for remedial learning used submicroscopic book. The response of students in the small-scale test was 78.02% (good) and the results of a large-scale test were 80.50% (good) and 81.17% (very good). The teachers also gave a positive response for use of the submicroscopic book and that was 86.67% (very good). The use of this submicroscopic book can be the one of solutions for implementing remedial teaching.